2018
DOI: 10.3390/gels4030075
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Hydrogels: Advances in Nanofillers Used for Nanomedicine

Abstract: The ongoing progress in the development of hydrogel technology has led to the emergence of materials with unique features and applications in medicine. The innovations behind the invention of nanocomposite hydrogels include new approaches towards synthesizing and modifying the hydrogels using diverse nanofillers synergistically with conventional polymeric hydrogel matrices. The present review focuses on the unique features of various important nanofillers used to develop nanocomposite hydrogels and the ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 88 publications
(99 reference statements)
0
44
0
2
Order By: Relevance
“…Previous studies have reported that the mechanical property of hydrogels can be enhanced by incorporating inorganic fillers, owing to the molecular interactions between polymer chains and the surface of inorganic fillers. [13,[34][35][36][37][38][39][40][41] We first hypothesized that the incorporation of mesoporous silica nanoparticles with high surface areas can contribute toward enhancing the cohesion property of the PAM/PDA hydrogels while maintaining their adhesive property. We synthesized mesoporous silica nanoparticles with extra-large mesopores (XL-MSNs) for this purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the mechanical property of hydrogels can be enhanced by incorporating inorganic fillers, owing to the molecular interactions between polymer chains and the surface of inorganic fillers. [13,[34][35][36][37][38][39][40][41] We first hypothesized that the incorporation of mesoporous silica nanoparticles with high surface areas can contribute toward enhancing the cohesion property of the PAM/PDA hydrogels while maintaining their adhesive property. We synthesized mesoporous silica nanoparticles with extra-large mesopores (XL-MSNs) for this purpose.…”
Section: Resultsmentioning
confidence: 99%
“…NC hydrogels have been categorized based on their stimulussensitivity which includes thermo-responsive, light-responsive, electro-responsive, and magnetic-responsive hydrogels. In addition, they have been classified based on their applications, such as in sensors, catalysts, drug delivery systems, wound dressings, and tissue engineering (Song et al, 2015;Vashist et al, 2018). They are also classified according to the type of incorporated nanomaterials, which is the more common type of classification (Sharma et al, 2018;Vashist et al, 2018;Rafieian et al, 2019).…”
Section: Nc Hydrogelsmentioning
confidence: 99%
“…In addition, they have been classified based on their applications, such as in sensors, catalysts, drug delivery systems, wound dressings, and tissue engineering (Song et al, 2015;Vashist et al, 2018). They are also classified according to the type of incorporated nanomaterials, which is the more common type of classification (Sharma et al, 2018;Vashist et al, 2018;Rafieian et al, 2019). Frequently reported nanofillers in NC hydrogels are silica such as nano-clay (Jin et al, 2018) and fumed silica (Kehr et al, 2013), carbon in the form of carbon nanotubes, graphene (Servant et al, 2014) and graphene oxide (GO) (Rasoulzadeh and Namazi, 2017;Tarashi et al, 2019), metal and metal oxide nanoparticles (Tan et al, 2019) such as gold, silver, iron oxide, titanium oxide (TiO 2 ), nanohydroxyapatite, alumina and zirconia, and polymeric nanoparticles such as nano-scaled cellulose (NSC) (Dutta et al, 2019), including cellulose nanofibers, nanocrystals, and nanowhiskers.…”
Section: Nc Hydrogelsmentioning
confidence: 99%
“…Such mechanical features render them quite difficult to handle, or to stabilize after injection in vivo. Therefore, the incorporation of NPs within the scaffold could help solve the mechanical stability issue . Moreover, iron oxide, gold, or carbon‐based NPs render the composite materials responsive to a wide range of external stimuli such as magnetic field, infrared light, or electric field .…”
Section: Introductionmentioning
confidence: 99%